Alcohol myopia and sexual abdication among women: Examining the moderating effect of child sexual abuse. (February 2015) - Staples, Jennifer M.; George, William H.; Stappenbeck, Cynthia A.; Davis, Kelly Cue; Norris, Jeanette; Heiman, Julia R.
Abstract: Introduction: HIV and other STIs are major public health concerns for women, and risky sexual behaviors increase the risk of transmission. Risky sexual behaviors include sexual abdication, that is, willingness to let a partner decide how far to go sexually. Alcohol intoxication is a risk factor for risky sexual behavior, and the Inhibition Conflict Model of Alcohol Myopia may help explain this relationship. This model suggests that in order for intoxication to influence behavior there must be high conflict, meaning the strength of the instigatory cues and inhibitory cues are both high. Recent research indicates that the degree to which cues are experienced as high in instigation or inhibition is subject to individual difference factors. One individual difference factor associated with alcohol-related sexual risk taking is child sexual abuse (CSA) history. Methods: The current study examined the influence of acute alcohol intoxication, CSA, and inhibition conflict on sexual abdication with 131 women (mean age 25) randomized into a 2 (alcohol, control) × 2 (high conflict, low conflict) experimental design. Results: Regression analyses yielded a significant 3-way interaction, F (1, 122) = 8.15, R 2  = .14, p  < .01. When there was high conflict, intoxicated CSA women were more likely to abdicate than sober CSA women, however, sober CSA women were less likely to abdicate than sober NSA women, when there was low conflict, CSA history and alcohol intoxication had no influence on abdication. Conclusion: These results may help explain the association between alcohol and risky sexual decision making among women with CSA. Highlights: We used an experimental design to examine in-the-moment sexual decision making. There was a 3-way interaction among CSA, alcohol, and inhibition conflict. With high conflict, intoxicated CSA women abdicated more than NSA women. With high conflict, sober CSA women abdicated less than sober NSA women. With low conflict, CSA history and alcohol had no influence on abdication.